1981
DOI: 10.1159/000275552
|View full text |Cite
|
Sign up to set email alerts
|

Changes of the Action Potential, the Summating Potential and Cochlear Microphonics in Experimental Endolymphatic Hydrops

Abstract: The changes of the action potential (AP), the summating potential (SP) and cochlear microphonics (CM) were investigated in reference to the grade of endolymphatic hydrops produced by endolymphatic sac obliteration in guinea pigs. In a few cases with minimum endolymphatic hydrops, super-normal AP was obtained. With an increase of endolymphatic hydrops, CM responses were reduced although AP responses at intensive stimulation were maintained relatively well. It is thought that the polarity of positive SP, as obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Objective assessment of endolymphatic hydrops using electrocochleography was reported in 1977 by Gibson and colleagues, 12 who described an enhanced negative summating potential as indicative of hydrops. This finding was later corroborated in animal studies 13,14 and is a method in wide clinical use today.…”
Section: Introductionmentioning
confidence: 58%
“…Objective assessment of endolymphatic hydrops using electrocochleography was reported in 1977 by Gibson and colleagues, 12 who described an enhanced negative summating potential as indicative of hydrops. This finding was later corroborated in animal studies 13,14 and is a method in wide clinical use today.…”
Section: Introductionmentioning
confidence: 58%
“…It is possible that P0 is primarily produced by a combination of CAP response and the DC component of the CM, the summating potential (SP). As mentioned in section 4.3, Flock and Flock (2000) found that static pressure caused a temporary hydrops of SM, and several studies have shown that hydrops of SM can result in increased SP (Kumagami et al, 1981; van Deelen et al, 1987). Salt et al (2009) found that apical injections of viscous HA resulted in increased CM distortion and increased SP, and attributed the observations to a mechanically induced change in transducer operating point.…”
Section: Discussionmentioning
confidence: 85%
“…Previously we [Kumagami et al, 1981] reported on AP, CM and SP in relation to the degree of experimental endolymphatic hydrops. In that report, CM responses decreased but AP responses showed relatively good output potential at intensive stimulation as endolymphatic hydrops was intensified.…”
Section: Discussionmentioning
confidence: 99%